Local Wisdom of the Sodong Buddhist Village Community in Water Resources Management - Hanif, Muhammad; Chasanatun, Fida; Wibowo, Anjar Mukti (Budapest International Research and Critics University, 2021)
This study aims to describe and explain the local wisdom of the people of Kampung Budha Sodong in managing water resources. The research was conducted using an ethnographic approach. The research was conducted for one year in Sodong Hamlet, Braceletkulon Village, Sampung District, Ponorogo Regency, East Java Province, Indonesia. Collecting data by observation, interviews, and recording documents. The validity of the data used a source triangulation technique, while the data analysis used a qualitative interactive model technique. From the research carried out, it can be found that the local values of the people of Kampung Budha Sodong in managing water resources are in the form of a philosophy of life, inner teachings, noble pitutur, unen-unen, and pamali. The local wisdom is the driving force, community guide and reference in planning, implementing and evaluating water resources and their utilization. So that the availability of water in this village is sustainable. This is one of the factors that make the lives of the people of Kampung Buddha harmonious.